Changes in leisure time physical activity, obesity-related morbidities, fatal and non-fatal CVD events and total mortality: Over 20-year follow-up in the opera study - Asla Suutari-Jääskö; Karri Parkkila; Hannu Vähänikkilä; Mikko Tulppo; Juha Perkiömäki; Heikki Huikuri; Olavi Ukkola (PLoS ONE, 2026)
Background The impact of changes in leisure time physical activity (LTPA) is not well-documented, especially when considering occupational physical activity (OPA). This study examines the effects of LTPA changes in workers with varying physical activity demands. Methods Part of the OPERA study, we tracked morbidities for over 20 years (P1, from 1993 to 2014) and mortality for over 8 years (P2, from 2014 to 2021–2022) with 599 participants. They were categorized into four LTPA groups (“sedentary,” “started,” “quit,” “active”) and two OPA groups (“office workers” and “occupationally physically active”). Results Maintaining regular LTPA was associated with lower incidence of hypertension, diabetes and metabolic syndrome (p-values 0.007, < 0.001 and <0.001 respectively). Non-fatal cardiovascular disease (CVD) events were more common (p = 0.006, HR 1.99, CI95% 1.22–3.26) in the “quit” group during P1, especially among “occupationally physically active” (p < 0.001, HR 2.29, CI95% 1.23–4.29). During P2, fatal CVD events were associated with being in the “sedentary” group (p = 0.042, HR 2.67, CI95% 1.04–7.03). This association was particularly evident among “office workers,” where belonging to the “sedentary” and “quit” groups was associated with a higher risk of fatal CVD events (p = 0.017, HR 5.45, CI95%1.36–21.91, and p = 0.025, HR 4.55, CI95% 1.21–17.19, respectively). Furthermore, total mortality was associated with being in the “sedentary” or “quit” groups (p = 0.029, HR 3.69, CI95% 1.14–11.93, and p = 0.009, HR 4.61, CI95%1.47–14.49, respectively). Conclusions Stopping LTPA in middle age was associated to higher risk for non-fatal CVD events in “occupationally physically active” individuals. Fatal CVD events were associated with a sedentary lifestyle in whole study population. Among “office workers,” both a sedentary lifestyle and stopping regular LTPA were associated with higher risks of fatal CVD events and all-cause mortality.